Collective Security under the Gulf Cooperation Council: problems and prospects - Мaқaнғaли Б. Қ. (Journal of Oriental Studies, 2018)
The Gulf Cooperation Council (GCC) is the short and more popular name of the organization of the Cooperation Council for the Arab States of the Gulf, which is most often found in the Arabic-language and English-language scientific literature. In this article, the author examines the main problems of the development of the GCC organization at the present stage, including the attempts of the participating countries to create an effective system of collective security. Despite the fact that more than thirty years have passed since the creation of the organization, but so far the GCC countries have not been able to fully integrate to ensure regional security. In this regard, the flagship of the intra-Arab integration processes, Saudi Arabia sees an outlet in broad political integration. However, the horizons of such integration are difficult to predict. On the one hand, at the time of the establishment of the organization, the issue of political integration was not fixed in the Charter of the Council. And, apparently, this was done deliberately taking into account the complex processes of the formation of regional states. But on the other hand, the issue of political integration of such close countries seemed inevitable, and only the time and political will of the elites are needed for this. Therefore, when at the end of 2011 the King of Saudi Arabia proposed the creation of the Gulf Union on the basis of the GCC, it seemed that this initiative would be the impetus for the organization to reach a new level. But the subsequent policies of some participating countries and the flaring “Qatari crisis” in 2017 clearly demonstrated the systemic nature of the problems in this organization, which hinder political integration. The methodology of the research is based on a comparative historical analysis, both the main political and military events, and the real policy of states (realpolitic).